2021
DOI: 10.1002/eqe.3597
|View full text |Cite
|
Sign up to set email alerts
|

A seismic fragility model accounting for torsional irregularity in low‐rise non‐ductile RC moment‐resisting frames

Abstract: Buildings characterized by torsional irregularity are notorious for their vulnerability to earthquakes. However, most fragility/vulnerability models used for regional seismic risk assessment fail to distinguish between buildings with torsionally balanced and unbalanced configurations. The present study aims to develop a seismic fragility model sensitive to torsional irregularity for low-rise non-ductile RC moment frame buildings. To this end, a numerical investigation centred on 13 three-storied plan-asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Ruggieri et al [13] also performed a pushover analysis on both regular and irregular RC buildings. Bhasker et al [14] developed a seismic fragility model that was sensitive to torsional irregularity for low-rise, non-ductile RC moment frame buildings. Manie et al [15] evaluated the damage and the collapse behavior of low-rise buildings with unidirectional mass irregularities in plan using a nonlinear static and incremental dynamic analysis (IDA), and the results showed that the adverse effects of plan irregularity on structural collapse safety were more pronounced as the number of stories increased.…”
Section: Introductionmentioning
confidence: 99%
“…Ruggieri et al [13] also performed a pushover analysis on both regular and irregular RC buildings. Bhasker et al [14] developed a seismic fragility model that was sensitive to torsional irregularity for low-rise, non-ductile RC moment frame buildings. Manie et al [15] evaluated the damage and the collapse behavior of low-rise buildings with unidirectional mass irregularities in plan using a nonlinear static and incremental dynamic analysis (IDA), and the results showed that the adverse effects of plan irregularity on structural collapse safety were more pronounced as the number of stories increased.…”
Section: Introductionmentioning
confidence: 99%
“…As a response surface meta-model, HDMR represents a large set of data in the form of simple closed-form multivariate polynomial equations. HDMR has been adopted in previous studies to develop seismic fragility curves [15,16] with a prominent level of accuracy and minimal computational cost.…”
Section: Introductionmentioning
confidence: 99%